2017
DOI: 10.3747/co.24.3229
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Post-Surgery Treatments in Rectal Cancer: A Long-Term Single-Centre Experience

Abstract: Background Our study evaluated long-term survival outcomes in rectal cancer patients treated with preoperative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The overall local recurrence, which is a surrogate measure of the efficacy of the local treatment, was 3.3% and closely reflects previously reported rates. 16,17 Although the German rectal cancer study had reported local recurrence rates of approximately 6%, 1 subsequent studies showed fewer local recurrences, 2,12,23 and a similar trend was seen in our study group as well (3.2% and 3.5% in the SD and HD groups, p = 0.8). The incidence of distant recurrence was also similar in the 2 radiation dose groups (17.4% in the SD group and 19.4% in the HD group; p = 0.36).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The overall local recurrence, which is a surrogate measure of the efficacy of the local treatment, was 3.3% and closely reflects previously reported rates. 16,17 Although the German rectal cancer study had reported local recurrence rates of approximately 6%, 1 subsequent studies showed fewer local recurrences, 2,12,23 and a similar trend was seen in our study group as well (3.2% and 3.5% in the SD and HD groups, p = 0.8). The incidence of distant recurrence was also similar in the 2 radiation dose groups (17.4% in the SD group and 19.4% in the HD group; p = 0.36).…”
Section: Discussionsupporting
confidence: 85%
“…8 Although some studies have reported an increased pathological response with dose escalation, others have been more cautious about this increased pathological response. [9][10][11][12] However, almost all of the studies have reported observing significantly improved benefits with radiation doses beyond 4500 cGy. In fact, a dose-response model derived from patients treated with external beam radiation and brachytherapy boost showed a dose response with increased pCR at higher doses.…”
mentioning
confidence: 99%
“…The standard treatment for locally advanced rectal cancer (LARC) is preoperative chemoradiotherapy followed by surgical resection with total mesorectal excision (TME) [2,3]. Especially for patients with mid-low rectal cancer and T3 or T4 stage, preoperative chemoradiotherapy can effectively reduce the tumor volume, increase sphincter preservation, decrease local recurrence, and have long-term survival benefits [4]. However, the therapeutic effect of preoperative chemoradiotherapy on patients with rectal cancer varies significantly among individuals, with only a few patients (9-37%) achieving a pathological complete response (pCR) after treatment [5].…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer, including rectal cancer, is the third most prevalent malignancy worldwide and a leading cause of cancer-related deaths in the developed world (1). Synchronous distant metastases are diagnosed in approximately 15-20% of rectal cancer patients, most commonly involving the liver (2).…”
Section: Introductionmentioning
confidence: 99%